2021
DOI: 10.1108/ci-03-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Application of semantic Web ontologies for the improvement of information exchange in existing buildings

Abstract: Purpose Facilitating the information exchange and interoperability between stakeholders during the life-cycle of an asset can be one of the fundamental necessities for developing an enhanced information exchange framework. Such a framework can also improve the successful accomplishment of building projects. This paper aims to use Semantic Web technologies for facilitating information exchange within existing building projects. Design/methodology/approach In real-world building projects, the construction indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The introduction and utilization of novel technologies within the Architecture, Engineering, and Construction (AEC) domain is commonly perceived to have improved the construction processes with the adoption of 3Dbased modelling methods. The incorporation of such technologies has also led to improvements in project quality in areas such as information exchange and interoperability, project management, construction management, and cost management (Chan et al, 2019;Sadeghineko & Kumar 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction and utilization of novel technologies within the Architecture, Engineering, and Construction (AEC) domain is commonly perceived to have improved the construction processes with the adoption of 3Dbased modelling methods. The incorporation of such technologies has also led to improvements in project quality in areas such as information exchange and interoperability, project management, construction management, and cost management (Chan et al, 2019;Sadeghineko & Kumar 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Adopting advanced technologies within the AEC domain further facilitated the construction process by applying Building Information Modelling (BIM). Incorporating these technologies also improved project quality, including information exchange, interoperability, project management, construction management, and cost management, among other areas [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…BIM has gained increasing attention within the Architecture, Engineering, and Construction (AEC) domain due to its capacity to enhance processes and associated technologies [8,9]. BIM involves a collection of tools, technologies, and protocols that facilitate the generation, storage, management, and sharing of digital representations encompassing buildings' physical and functional properties [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Sadeghineko and Kumar (2021) firstly outlined the framework previously developed for generating semantically enriched three-dimensional (3D) retrofit models. Secondly, they proposed a framework focusing on facilitating the information exchange and interoperability for existing buildings.…”
mentioning
confidence: 99%
“…They indicated that the application of AR could be most effective in the following four stages of a project lifecycle: design and constructability review session; construction operation; construction assembly; and site management and maintenance, including site management and inspection and defect. Sadeghineko and Kumar (2021) firstly outlined the framework previously developed for generating semantically enriched three-dimensional (3D) retrofit models. Secondly, they proposed a framework focusing on facilitating the information exchange and interoperability for existing buildings.…”
mentioning
confidence: 99%